AB1002 Determinants of Quality of Life, Labor-Market Status and Healthcare Utilization in Ankylosing Spondylitis Patients. (15th July 2016) - Pimentel-Santos, F.M.; Peyroteo, I.; Mourão, A.F.; Sousa, E.; Costa, J.; Santos, H.; Barcelos, A.; Pinto, P.; Fonseca, J.E.; Branco, J.C.; Barros, P.P.
Abstract : Background: Ankylosing Spondylitis (AS) typically affects young people, leading to progressive deterioration of physical function and quality of life (QoL) with higher use of healthcare services. Work disability and early retirement is also higher in AS patients than in the general population, with a remarkable negative impact on productivity and social costs. Objectives: The objectives of this study were to assess the gradient of AS severity, measured by several well-established scores, for QoL, labour-market status and healthcare services demand, in a group of AS patients. Methods: We collected cross-sectional data in patients under 65 years, concerning demographic characteristics, disease duration, time to diagnosis, BASDAI, BASFI, BASMI, SF-36, ASQoL, EQ-5D and evaluated the ASDAS. The number of appointments and emergency room visits during the year before and working status in active ages people, were also collected. To measure the gradient of AS on QoL scores, healthcare use and working status, regression models, with application of stepwise procedure for removal of statistically non-significant effects, were performed. Results: A total of 369 patients were included (62.3% men and 37.1% women), with a mean age of 45.4±13.2 years (range 20–79 years). For SF-36 and ASQoL, only BASDAI and BASFI scores matter and both mean higher value associated with lower health and it seems that a one point increase in one score is roughly equal to one point increase in the other score. The same conclusion holds for EQ5D. The only difference lies with the group of patients with 7–12 years of schooling, who have higher utility score than the others. The probability of being employed is negatively related to age and to BASMI. Only the BASFI is positively associated with the number of medical appointments. Age and ASDAS are the only determinants of emergency rooms visits. Conclusions: BASDAI and BASFAI, which are modifiable scores, are negatively associated with utility/ QoL scores. Age and BASMI (no modifiable scores) are negatively associated with being employed. In addition, earlier or later disease detection, have no influence on these gradients. Accuracy of therapy intervention has a pivotal role on impacts, more than a precise time in detection. Disclosure of Interest: None declared